Pervasiveness of Depression among Students in Medical Colleges of Majmaah University, KSA - Wajid Ara Asra, Nida Gulzar Zeb, Sawsan Mustafa Abdalla, Badar Almehmadi, Saira Farhan, Huda H.Abdrahman, Elsadig Y.Mohamed, Hala M.Elsabag, Shahad Mohammed Almehrijh (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Depression is a mental condition that is defined by chronic melancholy and a loss of interest in things that a person generally enjoys, as well as an inability to carry out everyday tasks for at least two weeks. "Students cope with a multitude of difficulties at college, including new lifestyle, friends, roommates, exposure to different cultures and alternate ways of thinking, and, at times, financial troubles. Students who do not feel capable or equipped to cope with the unfamiliar atmosphere of a college campus are more likely to develop depression. Objectives: This study aimed to determine the prevalence of depression among students in medical colleges of Majmaah University, Al Majmaah Saudi Arabia and to measure the rates of depression among students. Material and methods: This was a cross-sectional, observational study done on the medical students of Majmaah University in year 2019-2020. Depression, Anxiety and Stress Scale-21 (DASS-21), along with a pretested pre-coded Socio demographic, questionnaire was used. Prior ethical approval was taken from the institutional review board. Participants’ anonymity was ensured. Sample Type used was Multi stage Stratified sampling and sample size was 369 students. The data was analyzed using SPSS version 20. Results: A total of 369 students took part in the study out of which 185 (51%) were females and 184(49%) were males. After analysis it was found that only 14.9% of students were free from depression, 49.6% students had symptoms of mild depression, 21.7% had symptoms correlating with moderate depression and 13.8% students had severe depression symptoms. Moreover female students were found to have more percentage of moderate and severe depressive symptoms than the male students. Conclusion: Depression is quite prevalent among students in medical colleges of Majmaah University with more students falling under the category of mild to moderate depression. Females have more symptoms of depression than male students. There is need for proper mental health screening programs at community level to help the students to cope up with depression. Keywords: Depression, prevalence, university students, medical college